2021
DOI: 10.1101/2021.06.09.447754
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

An outbreak of SARS-CoV-2 with high mortality in mink (Neovison vison) on multiple Utah farms

Abstract: The breadth of animal hosts that are susceptible to severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) and may serve as reservoirs for continued viral transmission are not known entirely. In August 2020, an outbreak of SARS-CoV-2 occurred in multiple mink farms in Utah and was associated with high mink mortality and rapid viral transmission between animals. The outbreak's epidemiology, pathology, molecular characterization, and tissue distribution of virus within infected mink is provided. Infection … Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 46 publications
1
12
0
Order By: Relevance
“…Further, it is unlikely that a variant so effective at spreading in the human population would have evolved in a non-human population; as the mutations required to be successful in a human population may well be different due to differences in cell receptors, as well as behaviour. Common mutations appear in animal populations, such as N501T and Y453F in mink across different continents (Eckstrand et al 2021;Lu et al 2021), but are rarely found in human infections, and not in any of the VOCs. While it would be possible for a two-step evolutionary process wherein there is first some adaptation in an animal population, allowing the crossing of a fitness valley, followed by spillover and human adaptation through conventional transmission, it would once again be difficult to explain the intermediate sample we observe through this transmission process.…”
Section: Other Variants Of Concernmentioning
confidence: 99%
“…Further, it is unlikely that a variant so effective at spreading in the human population would have evolved in a non-human population; as the mutations required to be successful in a human population may well be different due to differences in cell receptors, as well as behaviour. Common mutations appear in animal populations, such as N501T and Y453F in mink across different continents (Eckstrand et al 2021;Lu et al 2021), but are rarely found in human infections, and not in any of the VOCs. While it would be possible for a two-step evolutionary process wherein there is first some adaptation in an animal population, allowing the crossing of a fitness valley, followed by spillover and human adaptation through conventional transmission, it would once again be difficult to explain the intermediate sample we observe through this transmission process.…”
Section: Other Variants Of Concernmentioning
confidence: 99%
“…Respiratory or fecal swabs: RNA extraction and SARS-Cov-2 reverse transcriptase (RT) real-time PCR was performed as described [18]. Following initial viral detection by PCR, three dog samples and one cat sample were submitted to University of Minnesota Genomics Center (Oakdale, MN 55128) for whole genome sequencing (WGS) [19].…”
Section: Sars-cov-2 Rt-pcrmentioning
confidence: 99%
“…In the vast majority of cases, non-human animals seem to experience subclinical or mild disease following infection with SARS-CoV-2. There are exceptions -infected mink, large felids in zoos, and the occasional pet dog or cat have presented with signs of a respiratory infection, including coughing, sneezing, ocular/nasal discharge, and increased respiratory effort (30)(31)(32). More severe disease has also been observed, with a report out of the United Kingdom hypothesizing that SARS-CoV-2 infection may be linked to myocarditis in pet dogs and cats (18), and mink farms reporting increased mortality during SARS-CoV-2 outbreaks (30).…”
Section: Discussionmentioning
confidence: 99%
“…There are exceptions -infected mink, large felids in zoos, and the occasional pet dog or cat have presented with signs of a respiratory infection, including coughing, sneezing, ocular/nasal discharge, and increased respiratory effort (30)(31)(32). More severe disease has also been observed, with a report out of the United Kingdom hypothesizing that SARS-CoV-2 infection may be linked to myocarditis in pet dogs and cats (18), and mink farms reporting increased mortality during SARS-CoV-2 outbreaks (30). Thus far, only a few animal species have demonstrated the ability to transmit virus to naïve conspecifics (deer mice, cats, ferrets, raccoon dogs, and white-tailed deer), and mink are the only animals that have definitively infected humans (33)(34)(35).…”
Section: Discussionmentioning
confidence: 99%